Selective Determinants of Low Bone Mineral Mass in Adult Women with Anorexia Nervosa - Andrea Trombetti; Laura Richert; François R. Herrmann; Thierry Chevalley; Jean-Daniel Graf; René Rizzoli (International Journal of Endocrinology)
We investigated the relative effect of amenorrhea and insulin-like growth factor-I (sIGF-I) levels on cancellous and cortical bone density and size. We investigated 66 adult women with anorexia nervosa. Lumbar spine and proximal femur bone mineral density was measured by DXA. We calculated bone mineral apparent density. Structural geometry of the spine and the hip was determined from DXA images. Weight and BMI, but not height, as well as bone mineral content and density, but not area and geometry parameters, were lower in patients with anorexia nervosa as compared with the control group. Amenorrhea, disease duration, and sIGF-I were significantly associated with lumbar spine and proximal femur BMD. In a multiple regression model, we found that sIGF-I was the only significant independent predictor of proximal femur BMD, while duration of amenorrhea was the only factor associated with lumbar spine BMD. Finally, femoral neck bone mineral apparent density, but not hip geometry variables, was correlated with sIGF-I. In anorexia nervosa, spine BMD was related to hypogonadism, whereas sIGF-I predicted proximal femur BMD. The site-specific effect of sIGF-I could be related to reduced volumetric BMD rather than to modified hip geometry.